(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
Cotton processing enterprises require a specific approach and systematic measures to reduce fire risk. This article examines the importance of fire safety in cotton processing, the main risk factors, and methods to mitigate these risks. The study analyzes the effectiveness of telemetry systems and safety measures in enhancing fire safety.